Teaching, inequalities and reconfiguration of teaching work in secondary schools during the pandemic - Arroyo, Mariela (Universidad Nacional del Litoral, 2021)
This article presents the results of a qualitative research that addresses the reconfiguration of teaching and teaching work at secondary schools in a region of the province of Buenos Aires after the interruption of in-person classes during the pandemic and as a consequence of pedagogical continuity policies. The way in which the pandemic revealed the mechanisms of social differentiation is analyzed considering its effects on the deepening of educational inequalities. By means of group interviews, this research collected the decisions of head teachers and teachers of secondary schools to preserve pedagogical links in a scenario that interrupts ‘doing in-person school’. These decisions account for a process of a particular appropriation of policies in each school under unequal symbolic and material realities. Appropriations are conditioned by the grammar of schooling, the organizational model, and the historical configuration of teaching work (the structure of the job, the available teaching knowledge) at secondary school. The change in schooling conditions –given the switch from in-person teaching to different forms of non-face-to-face teaching– tensed and altered dispositions and knowledge, thus exposing new inequalities.